tylertriebs
For the following system, use the second equation to make a substitution for y in the first equation.
3x + y = 2
y + 4 = 3x
answers
3x + 3x - 4 = 2
3x + 3 - 4x = 2
3x + 3x + 4 = 2
Delete
Share
This Question is Closed
jhonyy9
Best Response
You've already chosen the best response.
0
so than y+4=3x --- y=3x-4 and now substitute this value of y in first equation
3x +3x -4 =2
jhonyy9
Best Response
You've already chosen the best response.
0
can you continue ?
jhonyy9
Best Response
You've already chosen the best response.
0
do you need to solve this system ?
tylertriebs
Best Response
You've already chosen the best response.
0
no?
jhonyy9
Best Response
You've already chosen the best response.
0
so 6x=6 --- x=6/6 --- x=1
y=3x-4 so y=3*1-4 so y=3-4 so y=-1
tylertriebs
Best Response
You've already chosen the best response.
0
i dont understand
Abbie23
Best Response
You've already chosen the best response.
1
What work have you done?
jhonyy9
Best Response
You've already chosen the best response.
0
ok so indifferent but your first answer is right sure
ok ?
tylertriebs
Best Response
You've already chosen the best response.
0
ok